A Case Report of Percutaneous Transluminal Septal Myocardial Ablation in Patients with Hypertrophic Cardiomyopathy - Mohammad Hasan Namazi (پزشکی بالینی ابن سینا, 2004)
A number of patients with severe obstruction due to hypertrophic cardiomyopathy have derived benefit at least over the short-term from inventional infarction of a portion of the interventricular septum by the  infusion of alcohol into a selectively catheterized septal artery , with reduction of the outflow gradient and improvement in symptoms .